Clinical Trial Design for Immune-Based Therapy of Hepatitis B Virus - Gill, Upkar S.; Bertoletti, Antonio (Seminars in Liver Disease, 2017)
The treatment paradigm in hepatitis B virus is on the cusp of major development, with a multitude of novel agents undergoing testing for clinical efficacy. Such new immune therapies are urgently required for the treatment of chronic hepatitis B virus. The current direct antiviral therapies, although able to control viral replication and limit the progression to cirrhosis, require lifelong administration due to frequent viral rebound on treatment cessation, and immune modulation with interferon is only effective in a subpopulation of patients. Here the authors discuss novel agents in the pipeline along with whom and how best to utilize these immune therapies to achieve functional cure with defined treatment endpoints in chronic hepatitis B virus.
Keywords: chronic hepatitis B; T-cell therapy; toll-like receptor agonists; immune-tolerance; viral hepatitis